Prenatal exposures to mixtures of endocrine disrupting chemicals and children’s weight trajectory up to age 5.5 in the SELMA study - Katherine Svensson (Nature Portfolio, 2021)
Abstract Exposure to endocrine disrupting chemicals (EDCs) may impact early growth, although information is limited on exposure to combination of multiple EDCs. We aimed to evaluate the effect of prenatal exposure to EDC mixtures on birthweight z-scores and childhood weight trajectories. Twenty-six proven and suspected EDCs, were analyzed in prenatal urine and blood samples from 1118 mothers participating in the Swedish Environmental Longitudinal Mother and child Asthma and allergy (SELMA) study. Two growth parameters were estimated from each child’s weight trajectory from birth to 5.5 years of age: infant growth spurt rate and age at infant peak growth velocity (PGV). Weighted quantile sum (WQS) regression was used to estimate the mixture effect and identify chemicals of concern. A one-unit increase in the EDC mixture WQS index, was associated with decreased birthweight z-scores of 0.11 (95% CI − 0.16, − 0.06), slower infant growth spurt rate of 0.01 (95% CI − 0.03, − 0.01, on the log10 scale), and delayed age at infant PGV of 0.15 months (95% CI 0.07, 0.24) after adjusting for potential confounders. Stratified analysis by sex, showed that delayed age at infant PGV was mostly observed in girls with 0.51 months (95% CI 0.26, 0.76). Identified chemicals of concern included perfluorinated alkyl substances (PFAS), Triclosan, phthalates, non-phthalate plasticizers, bisphenols, polycyclic aromatic hydrocarbons, pesticides and PCBs. Prenatal exposure to EDC mixtures was associated with lower birthweight and altered infant weight gain trajectories.